Designing Environment-Based Interactive Multimedia for Enhanced Language Learning in Indonesian Language and Literature Education Program - Sitti Harisah; Ida Nur'aeni; Ulinsa Ulinsa; Asrianti Asrianti (STAI Hubbulwathan Duri, 2025)
Traditional teaching methods in the